Study on Synthesis and Characterization of Porous Microspheres with Pendant Amine Groups - Małgorzata Maciejewska; Yuliia M. Bolbukh (Adsorption Science & Technology, 2015)
Porous microspheres of glycidyl methacrylate cross-linked with trimethylolpropane trimethacrylate were prepared with toluene as porogen by suspension–emulsion polymerization. With increasing molar ratio of the functional monomer to cross-linker, the epoxy group content increases significantly, whereas the parameters of porous structure (specific surface area and total pore volume) decrease. To obtain adsorbents bearing functional groups, the porous methacrylate network was modified by subsequent treatment with diethylenetriamine. Polymers capacity towards Cu(II), Zn(II), Pb(II) and Cd(II) was investigated.